Impact of Tillage Depth and Planting Spacing on Plant Growth and Root Yield of Carrot (Daucus carota L.) - Mou, Fazana Akter; Hossain, Md. Mokter; Haque, Tamanna; Yasmin, Afsana (Journal of Tropical Crop Science, 2023)
This study aimed to explore the impact of tillage depth and plant spacing on carrot growth and yield. The experiment followed a two-factor design using a randomized complete block approach, with three replications. Factor A encompassed three tillage depths: 10 cm (D1), 15 cm (D2), and 20 cm (D3), while Factor B included three planting spacings: 25 cm x 5 cm (S1), 25 cm x 10 cm (S2), and 25 cm x 20 cm (S3). Plant height, leaf fresh weight, root length, fresh weight, diameter, and dry weight exhibited significant variations across different tillage depths and plant spacings. The most noteworthy results, including a maximum root length (17.97 cm), diameter (4.07 cm), fresh weight (99.33 g/plant), and dry weight (3.87 g/50 g), were observed in the D3S3 combination. Conversely, the D1S1 combination yielded the least favourable outcomes in terms of these parameters. The incidence of root cracking, rot, and branching in carrots was lowest in the D3S3 combination, followed by other combinations. These issues became progressively more prominent with lower plant spacing and shallower tillage depth. In terms of yields, the highest gross yield (35.67 t/ha) was achieved in the D3S1 combination, while the lowest (20.17 t/ha) was recorded in D1S3. Similarly, the D3S1 combination demonstrated the highest marketable yield (32.67 t/ha), whereas the lowest (17.00 t/ha) was observed in D1S3. The most favourable benefit-cost ratio was associated with D3S1, while the least favourable ratio was linked to D1S3. Notably, yield and yield components saw improvement with narrower spacing, while growth parameters exhibited enhancement with wider spacing. The study's findings suggest that higher tillage depth combined with reduced spacing led to increased gross and marketable yields, whereas lower tillage depth combined with greater spacing resulted in decreased yields. Among the various treatment combinations, the D3S1 combination consistently yielded the highest overall results in terms of yield and marketability.